Adaptive Physical Education Activity Modification For Physical Disability Student Independence: Modifikasi Aktivitas Pendidikan Jasmani Adaptif Bagi Kemandirian Siswa Disabilitas Fisik - Faris Riski Nuladany; Sumaryanti Sumaryanti (Academia Open, 2026)
General Background Inclusive physical education requires individualized pedagogical adaptations to ensure equitable participation and motor development for all learners. Specific Background Adolescents with upper-limb impairments face severe manipulative barriers during traditional sports without appropriate instructional accommodations, heavily restricting their autonomous learning. Knowledge Gap Current mainstream pedagogies rarely integrate STEP-based spatial adjustments alongside orthotic devices utilized strictly as educational aids rather than clinical interventions. Aims This Single-Subject Research investigates the application of customized motor tasks to foster autonomous participation for a physically marginalized eighth-grade adolescent. Results Following the intervention, the participant’s autonomy scores progressed from a stable baseline mean of 25.00 to an intervention mean of 37.33. The visual analysis demonstrated a zero percent data overlap, confirming consistent behavioral improvements in grasping, throwing, catching, and equipment management. Novelty This study pioneers the combination of non-clinical orthotic supports with scaffolded environmental adjustments to prioritize functional autonomy over mere athletic performance. Implications Mainstream institutions must adopt customized pedagogical frameworks and functional tools to promote true autonomous learning and social integration for marginalized populations. Highlights The STEP pedagogical framework significantly optimizes manipulative motor execution like grasping and throwing. Orthotic wrist supports function successfully as mainstream classroom aids rather than purely clinical tools. Scaffolded instructional strategies transition marginalized youth toward self-reliant participation in inclusive sports environments. Keywords Inclusive Education; Manipulative Motor Skills; STEP Framework; Single Subject Research; Wrist Support